THE EFFECTS OF TEST CHARACTERISTICS ON THE HIERARCHICAL ORDER OF READING SKILLS (Malaysian Journal of Learning and Instruction, 2017)
Purpose â€“ The study sought to determine the hierarchical nature of reading skills. Whether reading is a â€˜unitaryâ€™ or â€˜multi-divisibleâ€™ skill is still a contentious issue. So is the hierarchical order of reading skills. Determining the hierarchy of reading skills is challenging as item difficulty is greatly influenced by factors related to test characteristics. To examine the interaction between these factors and item difficulty, and determine the possibility of such a hierarchy, this study used the multifaceted Rasch approach.Methodology â€“ In this descriptive study, a 42-MCQ reading test was administered to 944 ESL lower secondary students, randomly selected from eleven Malaysian national-type schools in the Federal Territory of Kuala Lumpur and the state of Selangor. These student populations were selected as the development of reading ability was considered critical at this stage of schooling. The reading test items were identified according to the following aspects: Reading Skill Areas (Interpreting information, making Inference, Understanding figurative language, Drawing conclusions, Scanning for details and Finding word meanings), Context Type (Linear and Non-Linear), and Text Type (Ads, Notice, Chart, Story extract, Short message, Poem, Short news report, Brochure, Formal letter, Conversation, Long passage and weather forecast). Applying the Many-Facet Rasch model of measurement, the study analyzed student responses to the test items with the help of FACETS, version 3.7.1.4. Findings â€“ The findings showed that context types, skill areas, and text types differed in difficulty (p